Prevalence and Associated Factors of Anemia among Reproductive-Aged Women in Sayint Adjibar Town, Northeast Ethiopia: Community-Based Cross-Sectional Study. (8th August 2020) - Woldu, Berhanu; Enawgaw, Bamlaku; Asrie, Fikir; Shiferaw, Elias; Getaneh, Zegeye; Melku, Mulugeta
Abstract : Background . Globally, anemia affects one-fourth of the world population including 30% of nonpregnant reproductive-aged women. It has a number of causes including micronutrient deficiencies and chronic infections, inherited or acquired disorders of hemoglobin synthesis and red blood cell production, or survival alterations. The aim of this study was to assess the prevalence and associated factors of anemia among reproductive-aged women in Sayint Adjibar town, South Wollo Zone, Northeast Ethiopia. Methods . A community-based cross-sectional study was conducted from February to April among 359 reproductive-aged women (RAW). Systematic random sampling technique was implemented to select study participants. Sociodemographic, socioeconomic, and reproductive histories of study participants were collected using the structured and pretested questionnaire. Capillary blood and stool samples were collected from each study participant for hemoglobin and parasitological analysis, respectively. Data were entered into Epi Info version 7 and transferred to SPSS version 20 for analysis. Both bivariable and multivariable binary logistic regression models were fitted to identify associated factors of anemia. p value <0.05 was considered as statistically significant. Result . The median age of the study participants was 25 years. The overall prevalence of anemia was 24.2%. Among those anemic individuals, 49 (56.3%) were mildly anemic. Age category 36–49 years (AOR = 2.64; 95% CI: 1.05, 6.60), no formal educational status (AOR = 2.28; 95% CI: 1.06, 4.92), food insecurity (AOR = 1.92; 95% CI: 1.01–3.65), and body mass index of above 25 kg/m 2 (AOR = 0.27; 95% CI: 0.08–0.87) were found to be statistically significant with anemia. Conclusion . The prevalence of anemia in this study was found as a moderate public health problem. The prevalence was significantly associated with women who had no formal education and were of older age group and those women living with household food insecurity and with higher body mass index. Therefore, it is better to design appropriate interventional strategies to reduce reproductive-aged women anemia. These include information, education, and communication activities focused on reproductive-aged women with no formal education and life-cycle-focused food security rather than targeted to only infants and young children or pregnant women.